2019
DOI: 10.1136/annrheumdis-2019-215321
|View full text |Cite
|
Sign up to set email alerts
|

Swollen, but not tender joints, are independently associated with ultrasound synovitis: results from a longitudinal observational study of patients with established rheumatoid arthritis

Abstract: ObjectivesJoint swelling and tenderness are considered a proxy for inflammation in patients with rheumatoid arthritis (RA). With ultrasound-detected inflammation as reference, our objectives were to explore on patient and joint level the associations between ultrasound synovitis and joint swelling, tenderness and patient-reported joint pain (PRJP).Methods209 patients with established RA were examined six times during 12 months with assessment of 32 joints in upper/lower extremities for joint swelling/tendernes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…However, there is still a debate on how to grade the detected changes, and how to monitor US inflammatory symptoms [20]. Recently, it has been reported that swollen joints were strongly associated with US-detected synovitis (GS/PD score), reflecting ongoing inflammation, while this association was not found for tender joints [23]. Our results are consistent with these data-the significant correlations were confirmed between all the assessed US scores and SJC.…”
Section: Discussionsupporting
confidence: 91%
“…However, there is still a debate on how to grade the detected changes, and how to monitor US inflammatory symptoms [20]. Recently, it has been reported that swollen joints were strongly associated with US-detected synovitis (GS/PD score), reflecting ongoing inflammation, while this association was not found for tender joints [23]. Our results are consistent with these data-the significant correlations were confirmed between all the assessed US scores and SJC.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Hammer et al showed no association between tender joints and synovitis in GSUS and PDUS, while a strong correlation between swollen joints and US synovitis was calculated. In addition, they found a primary associationn between tender joints and patient-reported joint pain [38]. These findings support that the parameters of DAS28 hardly correlated with the sum scores of FOI also in this present study.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, low correlations have been shown between PROMs and MRI synovitis in RA patients [ 15 ]. Our findings are supported by a recent study of established RA patients that found swollen but not tender joints to be associated with US synovitis [ 5 ].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, swollen joint assessment has a high face validity and is a cornerstone in the clinical evaluation of joint inflammation in patients with RA. Furthermore, swollen joints have been found to be highly associated with disease evaluation by assessors and US synovitis in RA patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%